2015
DOI: 10.3390/ijms161126061
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Protects against Helicobacter pylori-Associated Gastritis by Combating Oxidative Stress

Abstract: Helicobacter pylori (H. pylori)-induced oxidative stress has been shown to play a very important role in the inflammation of the gastric mucosa and increases the risk of developing gastric cancer. Resveratrol has many biological functions and activities, including antioxidant and anti-inflammatory effect. The purpose of this study was to probe whether resveratrol inhibits H. pylori-induced gastric inflammation and to elucidate the underlying mechanisms of any effect in mice. A mouse model of H. pylori infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 44 publications
0
35
0
1
Order By: Relevance
“…It has been suggested that moderate drinking of red wine helps to prevent cardiovascular disease; resveratrol in red wine is believed to be the key molecule due to its inhibitory activities against platelet aggregation and oxidation of low-density lipoprotein (LDL) in blood [4]. Resveratrol is also recognized as a bioactive agent with potent anti-inflammatory, antioxidant, anti-proliferative, and cancer chemopreventive activities [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that moderate drinking of red wine helps to prevent cardiovascular disease; resveratrol in red wine is believed to be the key molecule due to its inhibitory activities against platelet aggregation and oxidation of low-density lipoprotein (LDL) in blood [4]. Resveratrol is also recognized as a bioactive agent with potent anti-inflammatory, antioxidant, anti-proliferative, and cancer chemopreventive activities [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Zhang et al. also indicated that mice treated with resveratrol (100 mg/kg b.w. for 6 weeks) could against H. pylori (10 8 CFU)‐induced IL‐8, iNOS, and NF‐κB expressions through activation of the Nrf2/HO‐1 pathway in gastric tissue.…”
Section: Gastroprotective Effects Of Phytochemicals and Their Underlymentioning
confidence: 99%
“…Some reports indicated that dietary phenolic compounds (curcumin, mangiferin, and β‐myrcene), phenolic acids (caffeic acid and ellagic acid), flavan‐3‐ols (catechin and (−)‐epigallocatechin‐3‐gallate [EGCG]), flavonols (quercetin and morin), flavonoids (resveratrol and pogostone), gingerols (6‐gingerol and 6‐shogaol), carotenes (lycopene and β‐carotene), and organosulfur ( s ‐allyl cysteine) possess multiple bioactivity and potential health benefits, such as antioxidant, anti‐inflammatory, and antibacterial benefits, and they can prevent digestive disease processes . In addition, some of the most beneficial phytochemicals also appear to increase antioxidant enzymes, mucosal defense, and the capacity to heal ulcers via upregulation of the Nrf2 signaling pathway, which may aid mucosal repair . These results suggest that Nrf2 expression induced by phytochemicals/pharmacological modulators may be a novel means of increasing GI protection.…”
Section: Gastroprotective Effects Of Phytochemicals and Their Underlymentioning
confidence: 99%
“…4). 이러한 결과는 땅콩새싹의 주성분으로 알려진 resveratrol이 폴리페놀계 파이토알렉신 (phytoalexins)의 작용 으로 항염증 작용이 우수한 것으로 알려져 있고 [19], 특히 포 도, 땅콩의 열매에서 발견되는 resveratrol은 대식세포, 지방 세포와 기질 혈관 세포에서 항염증 효과를 나타내고 있는 기 존 연구와 유사하다 [20]. 따라서 땅콩새싹 추출물에 포함되 어 있는 다수의 성분 중 resveratrol의 작용에 의해 NO의 생성 을 억제한 것으로 사료되며 NO에 의한 염증반응으로 나타나 는 피부 노화 및 주름생성을 지연시킬 수 있는 화장품 소재로 써의 가능성이 있는 것으로 사료된다.…”
Section: Raw 2647 세포에서 Reactive Oxygen Species (Ros)unclassified